Hydration kinetics and compressive strength of steam-cured cement pastes and mortars containing limestone filler. (15th June 2016) - Aqel, M.; Panesar, D.K.
Highlights: The effect of limestone filler (LF) on hydration kinetics and strength was evaluated.​ LF increased the heat of hydration, Ca(OH)2 content and early age strength. Increasing LF fineness increased the early age hydration and strength. Abstract: This paper aims to evaluate the influence of Limestone filler (LF) content and fineness on the hydration kinetics and strength of steam cured cement mortars and pastes. Experimental variables were cement fineness, LF content, LF fineness and steam curing duration. Mortar and paste specimens were steam cured at 55 °C for 12 and 16 h. Hydration kinetics were evaluated using heat of hydration and thermal analysis. The heat of hydration was measured using Isothermal Calorimetry. Calcium hydroxide (Ca(OH)2 ) content, calcium carbonate (CaCO3 ) content and degree of hydration were measured using Thermal Gravimetric Analysis and Differential Thermal Analysis. Compressive strength of mortars was evaluated at 12 h, 16 h, 3 days, 7 days and 28 days. The results showed increase in the heat of hydration, Ca(OH)2 content and early age strength (at 12 and 16 h) with the addition of LF. The results also revealed that the influence of LF on hydration kinetics and strength was influenced by the finenesses of the LF and the cement. In general, mix designs containing LF showed improved early age hydration and strength in mix designs made with higher cement fineness. Increasing LF fineness or cement fineness can reduce the negative impact of cement dilution by LF addition on the mechanical properties of mortars.